Six-year clinical study of firework-related eye injuries in North China. Issue 1071 (12th January 2015) - Kong, Yichun; Tang, Xin; Kong, Baohuan; Jiang, Hao; Chen, Ying
ABSTRACT: Purpose: To analyse the demographic data, clinical characteristics, management and prognosis of patients with firework-related eye injuries. Methods: A retrospective review was performed of patients with eye injuries related to fireworks referred to TianJin Eye Hospital in North China from 2008 to 2013. Demographic information, clinical features, management and visual outcome were analysed and prognosis factors were evaluated. Results: Ninety-nine patients (86 men) with 118 eye injuries were enrolled in the study. The average age of the patients was 32.0±20.5 years; 70/99 (70.7%) were aged >20 years. Eighty-one of the patients had been lighting the fireworks while the rest were bystanders. The main ophthalmic manifestations were hyphaema, vitreous haemorrhage, corneal/sclera/corneoscleral open globe injury, eyelid laceration, traumatic cataract, retinal/choroid detachment, endophthalmitis and intraocular foreign body (IOFB). Ninety patients required surgical intervention including repair of open globe injury, vitrectomy, cataract extraction and enucleation. 56/118 eyes (47.5%) received multiple operations. After treatment, final best-corrected visual acuity (BCVA) significantly improved (p=0.015). Some factors were significantly correlated with better final BCVA, including initial BCVA (p=0.036), closed globe injury (p=0.031), absence of endophthalmitis (p=0.014), absence of IOFB (p=0.024) and absence of retinal detachment (p=0.046). Conclusions: Firework-related eye injuries mainly occur in adult men and result in severe visual damage. The most common clinical manifestations are hyphaema and vitreous haemorrhage. Better initial BCVA and closed globe injury have a better visual result while endophthalmitis, IOFB and retinal detachment have a negative visual outcome. Improved eye protection, along with enhanced public education and legal ban on fireworks, could reduce the incidence of eye injuries.